If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -1x) = x + 2 (2 * 3 + -1x * 3) = x + 2 (6 + -3x) = x + 2 Reorder the terms: 6 + -3x = 2 + x Solving 6 + -3x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + -3x + -1x = 2 + x + -1x Combine like terms: -3x + -1x = -4x 6 + -4x = 2 + x + -1x Combine like terms: x + -1x = 0 6 + -4x = 2 + 0 6 + -4x = 2 Add '-6' to each side of the equation. 6 + -6 + -4x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = 2 + -6 -4x = 2 + -6 Combine like terms: 2 + -6 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 4x+36x=4x*h | | 5q-5=17 | | 2(3n-1)=(4n+8)+7 | | 2.00-.33=.22x | | 2t+6=21-t | | 5(5x+2)-9=25x+1 | | 8c=90-c | | 11-5y=4y+20 | | 65-5x=4x+23 | | 47x+1673x-15=43(40x+60) | | 11+5y=4y+20 | | 4(t+2)=18-t | | x^2+3x-2x=5x+1 | | .6x-4.2=.6 | | 93-5x=8x-15 | | 4x-2=11x-54 | | -4(3x-1)+7(3-2x)= | | 3(4x+3)+99=17x+4-5x+104 | | 0.5x-6+2x+0.5x=12 | | -118-10x=10x+22 | | 8+6x=2x-32 | | 1/2(x+8)=14 | | 4350-3915=87(50x-45) | | (x-3)/3=x/5 | | 11x+10=7x+2 | | 8x+3+5x-5=180 | | 35=10x+5y-15 | | x/8-5=-22 | | 9x+31x-9=8(5x+7) | | -3(t-2)+5t=4t-1 | | 10x+18=2x-2 | | 2x^2=x^3-x+1 |